Why firms make unilateral investments specific to other firms: the case of OEM suppliers - Kang, Min‐Ping; Mahoney, Joseph T.; Tan, Danchi (Strategic Management Journal, 2009)
Abstract This study examines why and under what conditions firms will make unilateral relationship‐specific investments to their transaction partners. We propose that firms are more likely to make such investments when the investment yields positive economic spillover values for other transactions with the same exchange partners as well as for third‐party transactions. We also model two types of positive inter‐project spillover effects that a transaction may generate: knowledge spillovers and reputation spillovers. We find empirical support for our developed theory in the context of Taiwanese suppliers of original equipment manufacturers. Copyright © 2008 John Wiley & Sons, Ltd.